Pulmonary hypertension in ANCA-associated vasculitis: a retrospective analysis: Pulmonary Hypertension in AAV - Baqir, Misbah; Singam, Narayana Sarma; DuBrock, Hilary (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: Little is known about pulmonary hypertension (PH) in antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV).Objectives: The aims of this retrospective study, in which echocardiography was used for detection of PH, were to identify the potential causes of PH in AAV and to analyze the risk factors for mortality.Methods: We performed a retrospective descriptive review of 97 patients who had AAV with PH at our institution from January 1, 1997, through December 31, 2015. These patients with PH were compared with 558 patients who had AAV without PH. Demographic and clinical data were abstracted from electronic health records.Results: Among the patients who had PH, 61% were men; mean (SD) age was 70.5 (14.1) years at the time of PH diagnosis. The majority of patients with PH (73.2%) had more than 1 potential cause of PH, with left heart disease and chronic lung disease being the most common causes. Older age, male sex, smoking history, and kidney involvement were associated with the presence of PH. PH was associated with an increased risk of death (hazard ratio, 3.15; 95% CI, 2.37-4.18). On multivariate analysis, PH, age, smoking status, and kidney involvement were independent risk factors for death. Median survival after the diagnosis of PH was 25.9 months (95% CI, 12.2-49.9).Conclusions: PH in AAV is often multifactorial, is commonly associated with left heart disease, and is associated with a poor prognosis.